Teaching Cobots in Learning Factories – User and Usability-Driven Implications - Schmidbauer, Christina; Komenda, Titanilla; Schlund, Sebastian (Procedia manufacturing, 2020)
Up to now, industrial robots were considered as machines working for humans. In this sense, programming required special coding knowledge and skills as teaching approaches were based on imperative programming methods, formulating the solving of a problem line by line. As novel work principles consider the robot rather a tool, assisting or collaborating with the human, declarative approaches are needed, that allow for intuitiveness and modifiability. Collaborative robot (cobot) control requires intuitive interfaces, not only for ease of use but also for modifying existing execution programs. Furthermore, the increasingly diverse personnel also requires a more democratic approach to robot programming. However, there is no standard or guideline for intuitive cobot control, and it can be noticed that the usability of the diverse interfaces and systems provided on the market is rather poor. This paper compares three systems with their advantages and disadvantages concerning usability and presents the results of the standard usability score (SUS) test, which was conducted in the Vienna learning factory “TU Wien Pilot Factory for Industry 4.0”. Additionally, the paper presents an approach on how to teach different levels of cobot interaction and control addressing the skill sets needed in their individual working environments.